Safety and Effectiveness of Rasburicase in the Control of Hyperuricemia in Pediatric Patients with Non-Hodgkin’s Lymphoma and Acute Leukemia: An Open-Label, Single-Arm, Multi-center, Interventional Study - Wang, Tianyou; Zhu, Xiaofan; Chen, Yumei; Shen, Shuhong; Tang, Yongmin; Zhang, Jingying; He, Yingyi; Zhang, Hui; Gao, Ju; Fang, Jianpei; Liu, Rong; Wu, Xiaoyan; et al. (Drugs in R&D, 2023)
Introduction Despite rasburicase's proven efficiency in Caucasians, Japanese, and Koreans, studies evaluating the safety and effectiveness of rasburicase in Chinese pediatric patients with non-Hodgkin’s lymphoma (NHL) and acute leukemia (AL) in particular are lacking. Objective The aim was to evaluate the safety and effectiveness of rasburicase in Chinese pediatric patients with NHL and AL. Methods In this phase IV, open-label, non-randomized, single-arm, multi-center, interventional study (NCT04349306), children newly diagnosed with NHL or AL who received 0.20 mg/kg/day of rasburicase were included. The primary objective was to assess the safety of rasburicase by the incidence of adverse events (AEs). The secondary objective was to determine the effectiveness of rasburicase in the control of hyperuricemia. Results Out of 50 patients, 25 reported a total of 76 treatment-emergent adverse events (TEAEs), including eight TEAEs of grade ≥ 3 in 12 patients. A drug-related serious AE was reported in one patient, and there was no incidence of death. The response rate in the intent-to-treat population was 100.0% (95% confidence interval 82.4–100.0) in patients ( n = 19) with baseline uric acid level of > 8.0 mg/dL. Similarly, the response rate was 86.2% ( n = 25) among 29 patients (60.4%) with baseline uric acid levels of ≤ 8.0 mg/dL. The maximum mean percentage decrease of plasma uric acid level in the overall patients was 96.9%. Conclusion Rasburicase was well tolerated and effective in controlling hyperuricemia in Chinese pediatric patients with NHL and AL.